A comparative study of mammography, sonography and infrared thermography in detection of cancer in breast - Badiger, Suresh; Moger, Jayant (International Surgery Journal, 2020)
Background: Breast cancer has emerged as the commonest cancer in Indian women. In a large population country like India we need a rapid, economical, and accurate investigation to diagnose breast cancer in its earlier stage. The objective of this study was to compare the effectiveness of mammography, sonography and infrared thermography in detection of breast cancer. Methods: Patients presenting to the surgical OPD with suspicious breast lump were evaluated by infrared thermography, sonography and mammography followed by biopsy of the breast lump. Results of the all 3 above radiological modalities were compared with the histopathological biopsy for the presence of the cancer. The study was done between 1st December 2012 to 31st August 2014 in Sassoon General Hospitals attached to B. J. Government Medical College, Pune. We compared the performance of all diagnostic methods individually and in combination using the results from all patients. Statistical analysis was performed for all variables with fisher’s exact test. Results: Out of 50 patients, 31 patients had malignant breast lesions and 19 patients had benign lesions on biopsy. The mammography showed higher diagnostic accuracy and specificity than ultrasonography and thermography. As an individual modality the sensitivity of the sonography was higher than mammography and thermography. Conclusions: Sonography is found to have higher sensitivity than mammography and infrared thermography but it is less specific than mammography. Mammography is found to be more specific (89.47%) than sonography and infrared thermography.